EFEKTIVITAS MODEL PEMBELAJARAN ISLAMI TERPADU UNTUK MENGOPTIMALKAN KECERDASAN IQ, EQ, DAN SQ ANAK USIA DINI - Martoyo; Rahma Wulandari; Anisa Juliana; Flora Ambarwati (widya balina, 2025)
This study aims to explore the effectiveness of an integrated Islamic learning model in optimizing intellectual (IQ), emotional (EQ), and spiritual (SQ) intelligence in early childhood at an integrated Islamic Early Childhood Education (PAUD) in Kotabumi. The study used a qualitative method with a case study approach. Subjects included teachers, parents, and children aged 4–6 years, while data were collected through participant observation, in-depth interviews, and learning documentation. The results indicate that the integrated Islamic learning model positively influences the development of children's IQ, EQ, and SQ. Activities such as reading the Hijaiyah alphabet, Islamic logic games, and Quranic stories enhance children's cognitive skills. Activities based on Islamic values, such as moral stories, empathy exercises, sharing, and group work, strengthen emotional intelligence, while prayer, Surah memorization, and the Prophet's example foster spiritual intelligence. The holistic integration of these three dimensions of intelligence creates intelligent, emotionally mature, and spiritually strong children.